Bilateral Multiple Lower Limb Tuberculous Aneurysms in a Pregnant Woman with Drug-Induced Liver Injury due to Tuberculosis Treatment - Farah Almadina; Kana Wulung Arie Ichida Prinasetyo; Dewi Roziqo; Irmi Syafa'ah (Jurnal Respirasi, 2025)
Introduction: Tuberculosis (TB) is a long-term infectious disease caused by Mycobacterium tuberculosis (MTB). It can occur during pregnancy, in which its treatment can cause side effects, such as drug-induced liver injury (DILI). Tuberculous aneurysm due to TB infection is a rare occurrence, which can spread directly and hematogenously from the vascular wall. We report a case of bilateral multiple lower limb tuberculous aneurysms in a pregnant woman with DILI due to TB treatment. Case: A 27-year-old pregnant woman at 14-15 weeks of gestation presented with painless lumps on the left side of her neck and both ankles. Fine needle aspiration biopsy (FNAB) of the left cervical lymph nodes confirmed tuberculous lymphadenitis. Vascular Doppler ultrasound of both lower limbs revealed multiple aneurysms, suspected to be infected tuberculous aneurysms with intramural thrombi, located on the lateral and anterior aspects of the distal leg extending to the left ankle, compressing the distal posterior and anterior tibial arteries. After one month of category one anti-TB drug (ATD) therapy, the patient developed elevated bilirubin levels (3.76 mg/dL). Following surgical intervention, the anti-TB regimen was resumed, leading to the resolution of the pseudoaneurysms by the fifth month of treatment. Conclusion: Tuberculous aneurysm in pregnant patients with TB is a rare and potentially life-threatening condition. It is difficult to diagnose, but TB infection should be considered a possible cause in endemic countries. Surgery combined with anti-TB treatment improves outcomes.